Mental health and quality of life in children and adolescents during the COVID-19 pandemic: a systematic review of longitudinal studies - Ester Orban; Lydia Yao Li; Martha Gilbert; Ann-Kathrin Napp; Anne Kaman; Sabine Topf; Maren Boecker; Maren Boecker; Janine Devine; Franziska Reiß; Flora Wendel; Flora Wendel; et al. (Frontiers Media S.A., 2024)
BackgroundThe COVID-19 pandemic has significantly impacted the mental health of children and families, i.e., due to measures like social distancing and remote schooling. While previous research has shown negative effects on mental health and health-related quality of life (HRQoL), most studies have focused on pre-post comparisons in the early pandemic stages. This systematic review aims to examine longitudinal studies to understand the long-term impacts of the pandemic on children and adolescents.MethodsThis systematic review adhered to the PRISMA guidelines and was preregistered in the international prospective register of systematic reviews (Record ID: CRD42022336930). We systematically searched PubMed/MEDLINE, Web of Science, PsycINFO, PSYNDEX, and the WHO-COVID-19 database and included studies published up to August 30, 2022. Based on pre-defined eligibility criteria, longitudinal and prospective studies that assessed the mental health or quality of life of children or adolescents (0-19 years) in the general population over a longer time span (at two or more measurement points) during the COVID-19 pandemic were included in the review. The methodological quality of the included studies was assessed using an adapted version of the Effective Public Health Practice Project (EPHPP) checklist. Narrative data synthesis was used to summarize the findings.ResultsA total of 5,099 results were obtained from literature searches, with 4,935 excluded during title/abstract screening. After reviewing 163 full-text articles, 24 publications were included in the review. Sample sizes ranged between n = 86 and n = 34,038. The length of the investigated time periods and the number of assessment points, as well as outcomes, varied. The majority of studies were of moderate methodological quality. Mental health outcomes were more frequently studied compared to measures of HRQoL. The findings from these studies mostly suggest that children and adolescents experienced heightened mental health problems, specifically internalizing symptoms like anxiety and depression. Further, there was a decline in their overall HRQoL over the course of the COVID-19 pandemic that did not necessarily subside when lockdowns ended.ConclusionIt is crucial to continue monitoring the mental health and well-being of children and adolescents following the pandemic to identify groups at risks and plan interventions. This should ideally be conducted by large systematic studies, using validated instruments, and encompassing representative samples to obtain reliable and comprehensive insights with the aim of improving youth mental health care.